Rola i znaczenie metody Otwartego Dialogu w Środowiskowych Centrach Zdrowia Psychicznego - Bartczak-Szermer, Dagmara; Rowiński, Tomasz (Studia Psychologica: Theoria et praxis, 2022)
The transformation of psychiatric mental health care in late 80s and 90s of the last century in Finland brought the results that were implemented by other countries. Reducing the percentage of people suffering from schizophrenia, a significant reduction in the patient's need for pharmacotherapy, reducing the costs of psychiatric care - by working with a specialized therapeutic team, involving the nearest community of people experiencing mental crises in the process of making decisions about treatment is the basis of the community care model. This model is gaining more and more popularity also in Poland. The Open Dialogue Method (ODA), consistent with the assumptions of deinstitutionalization and building a social support network in the local environment, was introduced to our country by the Polish Institute of Open Dialog Foundation. ODA promotes psychosocial and therapeutic interactions in which pharmacotherapy is not the first choice method. The article addresses the issues of both the transformation of psychiatric care and therapeutic methods that are effectively used by the Community Mental Health Centers. In the new model of care, the cooperation of specialists, the involvement of the social environment and focus on the use of environmental resources of people affected by mental crisis are an opportunity to significantly increase its effectiveness.